Substantiation of the method for constructing the diagram of the horizontal belt conveyor tightness - Koroviaka, Ye; Lubenets, T (National Mining University, 2017)
Purpose. The method for constructing the diagram of the conveyor belt tightness, which satisfies the fundamental conditions of the mechanical system equilibrium and takes into account the influence of its centrifugal forces has been substantiated. Methods. The horizontal conveyor belt tightness was determined experimentally, which allowed to draw the corresponding diagram. Findings. Regularities of the conveyor belt tightness distribution in a belt conveyor are established and a method for constructing a tightness diagram taking into account the influence of its centrifugal forces is developed. Originality. It is established that in a conveyor belt: – transmission of the traction force to the conveyor belt is carried out with a constant reaction on the drive station; – the tightness of the conveyor belt in the points of contact with the drive unit changes reciprocally; – the extension of the conveyor belt does not change. Practical implications. The method for constructing the diagram of conveyer belt tightness helps to increase efficiency of exploitation of the conveyor transportation-technological charts at mining enterprises.

Цель. Обоснование метода построения диаграммы натяжения конвейерной ленты, который отвечает фундаментальным условиям равновесия механической системы и учитывает влияние ее центробежных сил. Методика. Экспериментальное определение натяжения конвейерной ленты горизонтального ленточного конвейера и построение диаграммы ее натяжения. Результаты. Установлены закономерности распределения натяжений конвейерной ленты в ленточном конвейере и разработан метод построения диаграммы натяжения, учитывающий влияние ее центробежных сил. Научная новизна. Установлено, что в ленточном конвейере: – передача конвейерной ленте тягового усилия осуществляется при неизменной реакции на приводной станции; – натяжения конвейерной ленты на контактах с приводным блоком изменяются “зеркально”; – удлинение конвейерной ленты не изменяется. Практическая значимость. Метод построения диаграммы натяжения ленточного конвейера способствует повышению эффективности эксплуатации конвейерных транспортно-технологических схем горных предприятий.

Мета. Обґрунтування методу побудови діаграми натягу конвеєрної стрічки, який відповідає фундаментальним умовам рівноваги механічної системи і враховує вплив її відцентрових сил. Методика. Експериментальне визначення натягу конвеєрної стрічки горизонтального стрічкового конвеєра та побудова діаграми її натягу. Результати. Встановлено закономірності розподілу натягу конвеєрної стрічки у стрічковому конвеєрі та розроблено метод побудови діаграми натягу, що враховує вплив її відцентрових сил. Наукова новизна. Встановлено, що в стрічковому конвеєрі: – передача конвеєрній стрічці тягового зусилля здійснюється при незмінній реакції на привідній станції; – натяг конвеєрної стрічки на контактах з привідним блоком змінюються “дзеркально”; – подовження конвеєрної стрічки не змінюється. Практична значимість. Метод побудови діаграми натягу стрічкового конвеєра сприяє підвищенню ефективності експлуатації конвеєрних транспортно-технологічних схем гірничих підприємств.
Keywords: conveyor; conveyor belt; tightness; diagram; friction; block; equilibrium conditions; centrifugal forces